Implementation of Parate Executie Object of Liability - Redi Res (Lembaga Contrarius Indonesia, 2021)
Parate executive is the primary purpose of establishing Law Number 4 of 1996 concerning Mortgage Rights to provide solid legal protection for creditors holding mortgage objects. The easy and inexpensive execution process should make the parate executive the leading choice for creditors in auctioning mortgage objects if the debtor defaults. However, in reality, the parate execution could not be carried out properly because of the Supreme Court Decision No. 3210 K/Pdt/1984, in which one of the ratio decidendi in it that the public auction conducted by the Bandung KPKNL is invalid, and this is also supported by book II of the Supreme Court's guidelines which requires fiat execution from the District Court. This paper will explain how the two conflicting legal bases will impact the implementation of parate executives in the field. Keywords: Parate Executie; Mortgage; Land.